Pathways to resilience: adapting to sea level rise in Los Angeles. Issue 1 (19th September 2018) - Aerts, Jeroen C.J.H.; Barnard, Patrick L.; Botzen, Wouter; Grifman, Phyllis; Hart, Juliette Finzi; De Moel, Hans; Mann, Alyssa Newton; de Ruig, Lars T.; Sadrpour, Nick
Abstract: Los Angeles (LA) County's coastal areas are highly valued for their natural benefits and their economic contributions to the region. While LA County already has a high level of exposure to flooding (e.g. people, ports, and harbors), climate change and sea level rise will increase flood risk; anticipating this risk requires adaptation planning to mitigate social, economic, and physical damage. This study provides an overview of the potential effects of sea level rise on coastal LA County and describes adaptation pathways and estimates associated costs in order to cope with sea level rise. An adaptation pathway in this study is defined as the collection of measures (e.g., beach nourishment, dune restoration, flood‐proofing buildings, and levees) required to lower flood risk. The aim of using different adaptation pathways is to enable a transition from one methodology to another over time. These pathways address uncertainty in future projections, allowing for flexibility among policies and potentially spreading the costs over time. Maintaining beaches, dunes, and their natural dynamics is the foundation of each of the three adaptation pathways, which address the importance of beaches for recreation, environmental value, and flood protection. In some scenarios, owing to high projections of sea level rise, additional technical engineering options such as levees and sluices may be needed to reduce flood risk. The research suggests three adaptation pathways, anticipating a +1 ft (0.3 m) to +7 ft (+2 m) sea level rise by year 2100. Total adaptation costs vary between $4.3 and $6.4 bn, depending on measures included in the adaptation pathway.